Biochemical changes in stored donor units: implications on the efficacy of blood transfusion - Oyet, Caesar; Okongo, Benson; Onyuthi, Richard Apecu; Muwanguzi, Enoch (Journal of Blood Medicine, 2018)
Background: Blood transfusion with allogeneic blood products is a common medical intervention to treat anemia or prepare patients for surgical procedures. Generally, the blood units are secured and stored prior to expected transfusion. During storage, a number of biochemical changes occur (generally known as storage lesion), which can affect the efficacy of blood transfusion. The aim of the study was to evaluate the biochemical changes that occur in blood units during storage and to project the impact of these changes on transfusion. Methods: The study protocol was approved by the Faculty of Medicine Research Ethics committee of Mbarara University of Science and Technology. A total of 200 blood recipients were categorized into two study arms: group I received fresh blood (n=100) and group II received old blood (n=100), who were formally consented and recruited consecutively. A total of 2 mL of venous blood was collected from each participant in EDTA tubes before transfusion (for pre-transfusion hemoglobin [Hb] estimation) and after transfusion (for post-transfusion Hb estimation). Each cross matched unit was sampled to collect plasma for pH, lactate and potassium assays. Data were analyzed with STATA version 12.0. Results: A total of 200 blood transfusion recipients aged 1–60 years were enrolled in the study. Up to 60% of the participants were females. The pH of the stored blood dropped from 7.4 to 7.2 in the first 3 days to ~7.0 by day 11 and to <7.0 by day 35 (p=0.03). The average rise in lactate level was 25 g/dL in blood stored for 0 to 11 days and 32.4 g/dL in blood stored for 21–35 days. The highest increase was encountered in blood stored beyond 28 days: 40–57 g/dL by 35 days (p=0.001). Potassium levels equally increased from ~4.6 mmol/L in the first 5 days of storage to ~14.3 mmol/L by 11 days. From the third week of blood storage and beyond, there was exponential increase in potassium levels, with the highest record in blood units stored from 30 to 35 days (p=0.068). Conclusion: Whole blood stored for >14 days has reduced efficacy with increased markers of red cell storage lesion such as increased potassium level, lactate and fall in pH. These lesions increase the length of hospital stay.
Keywords: Blood transfusion; Storage lesion; Biochemical changes; Anemia; Uganda